2004
DOI: 10.1016/j.jcrs.2003.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Corneal pachymetry in normal and keratoconic eyes

Abstract: This study suggests that OII and US pachymetry provide similar readings for CCT in normal subjects when an LCF is used. In keratoconus patients, OII provides a valid clinical tool for the noninvasive assessment of CCT when the LCF is not applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 19 publications
2
48
2
3
Order By: Relevance
“…A second regression analysis (or analysis of residuals from a differences analysis) really needs to be routinely undertaken to quantify any bias (or demonstrate the lack of it), although this is actually rarely reported for comparisons between ophthalmic instruments. For example, just the Bland-Altman plot may be presented, even when the plots suggest a systematic bias [20], and a regression analysis on the difference between the two pachymeters would have been useful. An erroneous conclusion might be drawn that just because the 95% limits of agreement (±1.96 SD about the mean difference) have a narrow range (as in the present example, where the LoA is 0.038 to 0.096 mm, or a range for this of just 0.029 mm), then agreement between the two instruments is acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…A second regression analysis (or analysis of residuals from a differences analysis) really needs to be routinely undertaken to quantify any bias (or demonstrate the lack of it), although this is actually rarely reported for comparisons between ophthalmic instruments. For example, just the Bland-Altman plot may be presented, even when the plots suggest a systematic bias [20], and a regression analysis on the difference between the two pachymeters would have been useful. An erroneous conclusion might be drawn that just because the 95% limits of agreement (±1.96 SD about the mean difference) have a narrow range (as in the present example, where the LoA is 0.038 to 0.096 mm, or a range for this of just 0.029 mm), then agreement between the two instruments is acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…In these situations, scattering from corneal haze and stromal interfaces interferes with the identification of the corneal surface reflections due to the limited resolution of slit scanning. [21][22][23] The main drawback of ultrasound imaging is the inconvenient requirement of immersing the eye in a coupling fluid. Thus, a better method of pachymetric mapping is still needed.…”
mentioning
confidence: 99%
“…Corneal thickness has been proposed to be a useful parameter for the clinical identification of keratoconus. 36,37 Studies using ultrasound 38,39 or slit-scanning technologies40 have found that the difference (or ratio) between the peripheral and the thinnest (or central) corneal thickness was significantly greater in eyes with keratoconus than in normal eyes. Corneal thickness measurements have some disadvantages.…”
Section: Discussionmentioning
confidence: 99%